Peningkatan Hasil Belajar Peserta Didik Menggunakan Model Project Based Learning (PjBL) pada Pembelajaran IPAS di Kelas IV SD Negeri 17 Batu Gadang Kota Padang - Prastika, Novela; S, Farida; Arwin, Arwin; Engreini, Syofianti (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to improve the learning outcomes of students in Natural and Social Sciences (IPAS) learning through the application of the Project Based Learning (PjBL) model in grade IV of SD Negeri 17 Batu Gadang, Padang City. This research is a Class Action Research (PTK) which is carried out in two cycles, with a qualitative and quantitative approach. Each cycle consists of four stages, namely planning, implementation, observation, and reflection. The subjects of the study were 13 students of class IV. Data collection techniques include observation, documentation, tests, and non-tests. The results of the study show that the application of the PjBL model is able to improve the quality of learning and learning outcomes of students. There was an increase in the average score of learning outcomes from 70.88 in the first cycle to 81.10 in the second cycle. In addition, the quality of learning implementation by teachers and students also showed an increase in each cycle. Thus, it can be concluded that the Project Based Learning model is effective in improving the learning outcomes of IPAS in grade IV students of SD Negeri 17 Batu Gadang. This model can be used as an alternative innovative learning strategy to increase student involvement and understanding in the learning process.